2019
DOI: 10.9734/jeai/2019/v31i230067
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Soil Attributes, Accumulation of Foliar Macronutrients and Productivity of the 'Vitória' Pineapple Plant Fertilized with Urea and Chicken Manure

Abstract: The pineapple plant cultivar 'Vitória' is resistant to Fusarium and it presents similar characteristics to the cultivars 'Pérola' and 'Smoot Cayene'. However, the expansion of this new cultivar depends on the development of research on several aspects, among them, fertilization. In this context, the experiment was carried out with the objective of evaluating soil fertility, foliar macronutrient contents and productivity in 'Vitória' pineapple plant in function of nitrogen fertilization with urea and chicken ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…(Santos et al 2014) who studied the nutrition of pineapple crown sprouts, (Silva et al 2014), who studied the decomposition and release of nutrients from organic sources, and (Irineu et al 2018) studied the application of organic fertilizer in melons. Studies have shown the benefits of using organic fertilizers for crop growing, such as poultry litter in pineapple (Pereira et al 2019), humic acids in pineapple crown sprouts (Santos et al 2014), and biofertilizer based on bovine manure in melons (Irineu et al 2018). The decomposition and nutrient release from poultry little and cattle manure have also been studied (Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(Santos et al 2014) who studied the nutrition of pineapple crown sprouts, (Silva et al 2014), who studied the decomposition and release of nutrients from organic sources, and (Irineu et al 2018) studied the application of organic fertilizer in melons. Studies have shown the benefits of using organic fertilizers for crop growing, such as poultry litter in pineapple (Pereira et al 2019), humic acids in pineapple crown sprouts (Santos et al 2014), and biofertilizer based on bovine manure in melons (Irineu et al 2018). The decomposition and nutrient release from poultry little and cattle manure have also been studied (Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pineapple is a fruit plant with high nutritional demand, mainly for nitrogen (Leonardo et al 2019). Thus, sewage sludge and its derivatives can be used as nutrients source for this crop and as alternative in order to reduce its production costs (Mota et al 2018).…”
Section: Introductionmentioning
confidence: 99%